Genetic Diversity of African Trypanosomes in Tsetse Flies and Cattle From the Kafue Ecosystem - Nakamura, Yukiko; Hayashida, Kyoko; Delesalle, Victoire; Qiu, Yongjin; Omori, Ryosuke; Simuunza, Martin; Sugimoto, Chihiro; Namangala, Boniface; Yamagishi, Junya (Frontiers in Veterinary Science, 2021)
We clarified the genetic diversity of Trypanosoma spp. within the Kafue ecosystem, using PCR targeting the internal transcribed spacer 1 and the cathepsin L-like cysteine protease (CatL) sequences. The overall prevalence of Trypanosoma spp. in cattle and tsetse flies was 12.65% and 26.85%, respectively. Cattle positive for Trypanosoma vivax had a significantly lower packed cell volume, suggesting that T. vivax is the dominant Trypanosoma spp. causing anemia in this area. Among the 12 operational taxonomic units (OTUs) of T. vivax CatL sequences detected, one was from a known T. vivax lineage, two OTUs were from known T. vivax-like lineages, and nine OTUs were considered novel T. vivax-like lineages. These findings support previous reports that indicated the extensive diversity of T. vivax-like lineages. The findings also indicate that combining CatL PCR with next generation sequencing is useful in assessing Trypanosoma spp. diversity, especially for T. vivax and T. vivax-like lineages. In addition, the 5.42% prevalence of T. brucei rhodesiense found in cattle raises concern in the community and requires careful monitoring of human African trypanosomiasis.